PENGARUH HIDDEN CURRICULUM TERHADAP PEMBENTUKAN KARAKTER SISWA DI SMP IT MASJID SYUHADA’ KOTABARU YOGYAKARTA - Esti Rahmah Pratiwi (Jurnal Pendidikan Agama Islam, 2017)
Character building for student should be applied in the early age. It is important because early age is the crucial time for student to develop their potential ability. The purpose of this research is to determine the real form of character building through hidden curriculum theory. The research uses a quantitative method. The results showed that: 1) the implementation of the hidden curriculum in SMP IT (integrated Islamic of junior high school) Masjid Syuhada belong in a good category. With the highest percentage value of 29.54%, the group score indicates as good criteria. 2) Character building in the 2 grade of SMP IT (integrated Islamic of junior high school) Masjid Syuhada categorized as good enough, with the highest percentage value of 27, 28%. The group score indicates as good enough criteria. 3) There is a positive and significant influence of hidden curriculum in the student's character, as if the score of hidden curriculum increased by 0.649. Hidden curriculum influence 52.7% in student’s characteristic, while 47.3% are influenced by other factors.